Analisis Pengembangan Wisata Halal di Pantai Siring Laut dalam Perspektif Global Muslim Friendly Tourism - Imroatun Azizah; Ahmad Yunadi (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to analyze the development potential of halal tourism at Siring Laut Beach, Kotabaru Regency, based on the Global Muslim Friendly Tourism (GMFT) perspective. The research employs a qualitative method with a descriptive approach to provide a comprehensive understanding of the destination's readiness to meet halal tourism standards. Data were collected through observations, interviews with relevant stakeholders, documentation, and literature reviews. The analysis was conducted using the 4A tourism framework (Attraction, Accessibility, Amenities, and Ancillary) alongside the ACES framework (Access, Communication, Environment, and Services). The findings indicate that Siring Laut Beach possesses significant potential as a halal tourism destination due to its attractive coastal scenery, family-friendly atmosphere, and supportive accessibility. However, several aspects require further improvement, including the provision of halal-certified food and beverages, adequate worship facilities, halal tourism branding and promotion, service quality enhancement, and stronger institutional support. The study concludes that optimizing these elements is essential for enabling Siring Laut Beach to fulfill Global Muslim Friendly Tourism standards and strengthen its competitiveness as a sustainable halal tourism destination.